1995
DOI: 10.1128/jvi.69.10.6259-6264.1995
|View full text |Cite
|
Sign up to set email alerts
|

In vivo pathogenic properties of two clonal human immunodeficiency virus type 1 isolates

Abstract: We have investigated the in vivo pathogenic properties of two molecularly cloned strains of human immunodeficiency virus type 1 (HIV-1), HIV-1 NL4-3 and HIV-1 JR-CSF , in human fetal thymus/liver implants in severe combined immunodeficient mice. Studies comparing their in vivo replication kinetics and abilities to induce CD4 ؉ thymocyte depletion were performed. HIV-1 NL4-3 replicated in vivo with faster kinetics and induced greater levels of CD4 ؉ thymocyte depletion than did HIV-1 JR-CSF. These results demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
27
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 33 publications
7
27
0
Order By: Relevance
“…Thymocytes infected with HIV-1 JR-CSF demonstrated a less severe depletion of CD4bearing cells; depletion of cells with low levels of surface expression of CD4 and CD8 (CD4CD8 DP dim) was most ap-parent. Analysis of replication kinetics by ELISA for viral p24 antigen production in the supernatant revealed that the replication rate of HIV-1 NL4-3 was slightly greater than that of HIV-1 JR-CSF (data not shown), as has been observed in infected Thy/Liv implants in SCID-hu mice (20).…”
Section: Hiv-1 Proviral Distribution In Thymocytesmentioning
confidence: 69%
See 3 more Smart Citations
“…Thymocytes infected with HIV-1 JR-CSF demonstrated a less severe depletion of CD4bearing cells; depletion of cells with low levels of surface expression of CD4 and CD8 (CD4CD8 DP dim) was most ap-parent. Analysis of replication kinetics by ELISA for viral p24 antigen production in the supernatant revealed that the replication rate of HIV-1 NL4-3 was slightly greater than that of HIV-1 JR-CSF (data not shown), as has been observed in infected Thy/Liv implants in SCID-hu mice (20).…”
Section: Hiv-1 Proviral Distribution In Thymocytesmentioning
confidence: 69%
“…SCID-hu mice. CB-17 mice homozygous for the SCID defect were bred at the University of California at Los Angeles and housed as described previously (20). Construction of the SCID-hu (Thy/Liv) mouse, using fetal tissue between 18 and 23 weeks of gestational age, has been described previously (2,30,32).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The cloning of single HIV-1 from the clinical isolate is a useful method for analysis of the properties of the isolate. Infectious molecular clones have been prepared from clinical isolates and their properties have been investigated (13).…”
Section: Discussionmentioning
confidence: 99%